Utilization of Nonsteroidal Anti-Inflammatory Drugs Among Physicians in General Outpatient Unit of University of Ilorin Teaching Hospital, Ilorin - Jamiu , M. O.; Giwa, A.; Abu-Saeed , K. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Nonsteroidal anti-inflammatory drugs are medications used to relieve pain, fever and inflammation. Serious toxicity related to gastrointestinal tract, kidney, dermatological and spontaneous abortion during early pregnancy are of serious concern in their use. The study evaluated the utilization of nonsteroidal anti-inflammatory drugs among prescribers at General Outpatient Department of the University of Ilorin Teaching Hospital. Retrospective study of 1297 patient prescription sheets was carried out at General Outpatient Department of the University of Ilorin Teaching Hospital for a period of six months to evaluate prescribing pattern of nonsteroidal anti-inflammatory drugs by Physicians. Data obtained were analyzed using Statistical Package for Social Science. Data were presented in the form of text, frequency tables, bar chart and pie chart. Inferential statistics was done using logistic regression and chi square. Out of 1497 prescription sheets studied, 1297 contained NSAIDs, giving prescribing rate of 86.6%. About 7.3% of prescriptions contained more than one NSAID. The percentage of generic prescribing was found to be 45%. About 17% of the prescribed NSAIDs were of long time use with only 0.04% co-prescribed with gastro-protective agent, omeprazole or misoprostol. Diclofenac tablet was the most prescribed NSAID with 42.2% prescribing rate. There was no significant difference in duration of prescribed NSAIDs and number of prescribed medicines per prescription in relation to patient’s gender. The prescribing rate of nonsteroidal anti-inflammatory drugs was high with associated multiple NSAIDs use. Diclofenac tablet was the most widely prescribed. Co-prescribing of nonsteroidal anti-inflammatory drugs with gastro-protective agents was found to be very low.